Feminist Discourse in the Indonesian Subtitles of Disney’s Mulan (2020) - Simorangkir, Joyce Trinita; Zahwa, Salshabila; Siagian, Mutia Hanum; Pramana, Alberto (Lexeme : Journal of Linguistics and Applied Linguistics, 2026)
This paper investigates how feminist discourse is represented in the Indonesian subtitles of Disney’s Mulan (2020). The research aims to find out if feminist messages of empowerment, equality, and resistance to patriarchal norms are preserved, reconstructed, or neutralized across languages. By applying a descriptive qualitative method, data were taken from selected English–Indonesian subtitle pairs in the official Disney+ Hotstar version. Dialogues expressing the meaning of feminism were thematically grouped into empowerment and self-agency, resistance to patriarchy, and ideological neutralization. The analyses utilized the concepts of feminist discourse theory by Tong (2009) and Butler (1990), and audiovisual translation frameworks by Díaz-Cintas and Remael (2007). The results show that while most liberal feminist ideas of autonomy and agency have been successfully preserved in subtitles, some expressions of resistance have been softened partially in order for them not to violate Indonesian cultural values. This ideological negotiation can be seen as an example of how translation functions not only as a mere linguistic transfer but rather as one of the modes of cultural mediation as well. Hence, subtitling is crucial for the interpretation of global feminist narratives by local audiences.